Spiral coil beneath fingertip enhances tactile sensation while tracing surface with small undulations. (4th March 2021) - Takei, Toshinobu; Ni'izeki, Tetsuya; Ando, Mitsuhito; Mochiyama, Hiromi; Imanishi, Etsujiro; Fujimoto, Hideo
ABSTRACT: We found that a spiral coil placed beneath a fingertip enhances tactile sensation while tracing small undulated surfaces. Hence, we investigated the mechanism underlying the enhanced tactile sensation. We evaluated the amplification effect quantitatively to demonstrate that the coil increases the tactile sensation in the finger pad. Specifically, we installed a strain gauge between the spiral coil and the fingertip to measure the strain corresponding to the curvature of a skin surface that undergoes deformation when tracing the surface. Then, to determine the enhancing mechanism of tactile sensation by the coil, we modeled the coil while moving on a surface with irregularities. The corresponding simulation results show that the inclination of the coil elements changes while moving on uneven shapes. Furthermore, as the distance between the tips of adjacent coil elements increases (reduces), the shape (or curvature) of the skin varies, and the skin on the fingertip attached to the coil expands (contracts) along the lateral direction. Therefore, the lateral strain on the fingertip is amplified by the coil moving on an undulated surface, thus enhancing tactile sensation. GRAPHICAL ABSTRACT: UF0001